Middle grounds : essays on midlife mothering - Mantas, Kathy, 1966-; Peterson, Lorinda, 1956- (Demeter Press, 2018)
Although motherhood writings are rich and emerging, the available literature on midlife motherhood and mothering is incomplete and often presented from a narrow perspective. Middle Grounds: Essays on Midlife Mothering fills this gap, widening the lens on a sociological phenomenon that is expanding in the twenty first century. It brings together scholarly and creative essays from diverse disciplines and cultural perspectives to reflect a more contemporary viewpoint -- that motherhood and mothering is not limited by the stages of life or chronological age. It echoes distinct voices speaking abou.